Incorporating Environmental Education in English Language Teaching through Bloom’s Revised Taxonomy - Defne Erdem Mete (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
It has become undeniable that language learners should be aware of global problems. One of the most serious problems of our globe today is the environmental degradation and education practices should have a contribution to ecological conservation. Environmental education, which is a developing field of study, aims to equip learners with the skills to identify and take action against ecological problems. In order to be able to take part in this solution process, English language learners should especially have critical thinking and critical reading skills. This paper suggests using Bloom’s Revised Taxonomy in an environmental education framework for fostering English language learners’ skills required for critical reading of authentic texts related to ecology and increasing their environmental awareness. In this respect, first, an application of the taxonomy in Monroe & Andrews et al.’s (2007) Environmental Education Strategies Framework is presented. Then, in order to exemplify the use of the taxonomy with an environmental education perspective, a set of reading questions which can be used for the critical reading of an authentic text is suggested. Our Iceberg is Melting: Changing and Succeding Under Any Conditions (2005), written by John Kotter and Holger Rathgeber as a fable, has been chosen as the sample authentic text. It is concluded that environmental education practices can be incorporated in English language teaching by fostering critical reading skills with the suggested approach and authentic texts on ecological issues can be used as classroom material for this purpose.